Adrenaline improves regional cerebral blood flow, cerebral oxygenation and cerebral metabolism during CPR in a porcine cardiac arrest model using low-flow extracorporeal support. (November 2021) - Putzer, Gabriel; Martini, Judith; Spraider, Patrick; Abram, Julia; Hornung, Rouven; Schmidt, Christine; Bauer, Marlies; Pinggera, Daniel; Krapf, Christoph; Hell, Tobias; Glodny, Bernhard; Helbok, Raimund; et al.
Abstract: Background: The effects of adrenaline on cerebral blood vessels during cardiopulmonary resuscitation (CPR) are not well understood. We developed an extracorporeal CPR model that maintains constant low systemic blood flow while allowing adrenaline-associated effects on cerebral vasculature to be assessed at different mean arterial pressure (MAP) levels independently of the effects on systemic blood flow. Methods: After eight minutes of cardiac arrest, low-flow extracorporeal life support (ECLS) (30 ml/kg/min) was started in fourteen pigs. After ten minutes, continuous adrenaline administration was started to achieve MAP values of 40 (n = 7) or 60 mmHg (n = 7). Measurements included intracranial pressure (ICP), cerebral perfusion pressure (CePP), laser-Doppler-derived regional cerebral blood flow (CBF), cerebral regional oxygen saturation (rSO2 ), brain tissue oxygen tension (Pbt O2 ) and extracellular cerebral metabolites assessed by cerebral microdialysis. Results: During ECLS without adrenaline, regional CBF increased by only 5% (25th to 75th percentile: −3 to 14; p = 0.2642) and Pbt O2 by 6% (0–15; p = 0.0073) despite a significant increase in MAP to 28 mmHg (25–30; p < 0.0001) and CePP to 10 mmHg (8–13; p < 0.0001). Accordingly, cerebral microdialysis parameters showed a profound hypoxic-ischemic pattern. Adrenaline administration significantly improved regional CBF to 29 ± 14% (p = 0.0098) and 61 ± 25% (p < 0.001) and Pbt O2 to 15 ± 11% and 130 ± 82% (both p < 0.001) of baseline in the MAP 40 mmHg and MAP 60 mmHg groups, respectively. Importantly, MAP of 60 mmHg was associated with metabolic improvement. Conclusion: This study shows that adrenaline administration during constant low systemic blood flow increases CePP, regional CBF, cerebral oxygenation and cerebral metabolism.